Enhanced upwelling and phosphorite formation in the northeastern Pacific during the late Oligocene: Depositional mechanisms, environmental conditions, and the impact of glaciio-eustacy: - Schollhorn, I.; Houben, A.J.P.; Gertsch, B.; Adatte, T.; Alexey, U.; Kaenel, E. de; Spangenberg, J.E.; Janssen, N.; Schwennicke, T.; Follmi, K.B. (2019)
The late Oligocene–early Miocene interval records a discernable episode of phosphorite formation, which is considered as the first of four main phosphogenic episodes during the late early and late Cenozoic. In order to better constrain the processes leading to widespread phosphorite formation we present new radiometric, geochemical, palynological, and sedimentological data from a drill core of the Roca Fosfórica Mexicana phosphorite mine at San Juan de la Costa, Baja California Sur (Mexico). In this region, phosphogenesis was enabled by the combination of high productivity and low sediment-accumulation rates due to enhanced upwelling and low detrital input related to regionally dry climate conditions. Phosphatic particles were formed in a shallow and well-oxygenated setting, subsequently concentrated by winnowing, and transported by gravity currents, which were mostly triggered by seismic activity. Following their deposition in a deeper and less well oxygenated setting pervasive phosphogenesis contributed to cementing the accumulated phosphatic grains. Correlation with global paleoclimate records suggests that this phosphogenic episode was linked to the expansion of the Antarctic ice sheet. Glacial weathering and the establishment of large-amplitude glacio-eustatic variations enhanced phosphorus supply on a global scale. Both glacial and interglacial phases participated in enhancing primary productivity in oceans, increasing the phosphorus flux into sediments, and favoring phosphogenesis, with glaciation being the prime cause. In addition, radiometric ages obtained in this study (28.62, 28.1, 27.19, 27.08, and 26.94 Ma) indicate that the onset of the late Oligocene–early Miocene phosphogenic episode was diachronous on a global scale with 2–3 m.y. older ages in the eastern Pacific in comparison to the Mediterranean and central Atlantic. This delay is explained by regional differences in paleoenvironmental and paleoceanographic conditions.